Managing scientific information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Managing scientific information in a small island nation: the Seychelles experience by Alex Mend and Peter Ballantyne 1992 23p published jointly by the International Service for National agricultural Research (ISNAR) and CTA